2018
DOI: 10.3389/fneur.2018.00574
|View full text |Cite
|
Sign up to set email alerts
|

Salivary IL-1ß as an Objective Measure for Fatigue in Multiple Sclerosis?

Abstract: Background: The causes of fatigue in multiple sclerosis (MS) and other inflammatory disorders are not well understood. One possible cause that might explain fatigue in inflammatory disorders appears to be the immunological process itself, triggering neural activity that is experienced as fatigue.Objectives: To investigate whether salivary IL-1ß concentration, associated with systemic inflammation, is related to subjective fatigue in MS.Methods: 116 MS patients (62 relapsing remitting MS, 54 secondary progressi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 62 publications
(55 reference statements)
1
4
0
Order By: Relevance
“…Anti-inflammatory cytokines were found to be associated with lower depression scores The biological functions and health effects of this inflammatory marker, however, require further investigation. Our mean cytokine results are similar to those reported in other studies that reported IL-1β in saliva (Hanken et al, 2018) and IL-6 and IL-10 in blood in adults with MS (Sorenson et al, 2013). It should be noted that our study discussed time of saliva collection while others did not.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Anti-inflammatory cytokines were found to be associated with lower depression scores The biological functions and health effects of this inflammatory marker, however, require further investigation. Our mean cytokine results are similar to those reported in other studies that reported IL-1β in saliva (Hanken et al, 2018) and IL-6 and IL-10 in blood in adults with MS (Sorenson et al, 2013). It should be noted that our study discussed time of saliva collection while others did not.…”
Section: Discussionsupporting
confidence: 91%
“…Even though we adhered to careful and standardized methods for saliva collection of cytokines, additional studies are needed in a larger sample to control for confounders (e.g., prior studies used blood measured cytokines; Milrad et al, 2018;Sorenson et al, 2013;Schmidt et al, 2016;Tsuboi et al, 2018;Wiener et al, 2019). However, we expect that the impact of these confounders is small because several authors have measured cytokines with saliva (Ghazali et al, 2017;Hanken et al, 2018;Szabo et al, 2016;Williamson et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…Recently, Hanken et al reported associations between salivary interleukin-1-beta and MS fatigue. 61 It has generally been challenging to identify clinically useful cytokine biomarkers of inflammation in MS because cytokines are locally acting and short lived.…”
Section: Discussionmentioning
confidence: 99%
“…These inflammatory factors can both act directly on the central nervous system and affect the HPA axis [10, 11]. Some scholars also have found that elevated levels of IL-1 β in peripheral blood activate the vagus nerve, which in turn leads to fatigue [12].…”
Section: Introductionmentioning
confidence: 99%